Preparation and characterization of H3PO4-modified cerium oxide catalysts for ethylene production from ethanol dehydration - Chong, Soo Ling (2017)
Ethylene production from ethanol dehydration offers an alternative synthesis route to the current synthesis route that is heavily dependent on the finite fossil fuel. Previous research works on ethanol catalytic dehydration focused the issue of catalyst coke formation. To minimize carbon deposition and to search for new ethanol dehydration catalyst, cerium oxide and H3PO4 were employed as dehydration catalysts owing to its coke-resistance as well as acidity properties. The objectives of this study are to investigate the effects of H3PO4 loading, reaction temperature and partial pressure on the catalytic performance on ethanol dehydration over cerium oxide and phosphorus-modified cerium oxide catalysts. New catalysts were employed for this reaction. For the modified catalysts, the wet impregnation technique was employed to prepare phosphorus modified cerium oxides with 10, 20 and 30 wt% of H3PO4 loadings. Subsequently, physicochemical properties were obtained through BET, XRD, XPS, TGA, SEM dan EDX analysis. The ethanol catalytic dehydration over the as-synthesized catalysts were carried out in a fixed-bed reactor at temperatures that ranged 673 to 773 K and 16 to 67 kPa of ethanol partial pressure. The XRD profiles showed that as the phosphorus loading was increased, the crystallinity has reduced. Both the BET specific surface area and mesopore volume decreased with H3PO4 loading, to the tune of nearly 90% reduction for the 30wt%H3PO4 loading. Significantly, the acid strength from the NH3-TPD analysis showed that 30PA-CeO2 has the highest amount of acid site which were of predominantly moderate-strength. Activity evaluation showed that the pure CeO2 offered little activity, while the H3PO4-modified ceria catalysts offered high ethanol catalytic dehydration activity (12-65.8% conversion) and high selectivity to ethylene (37-99%). Overall, the ranking in terms of activity was: 30PA-CeO2 > 20PA-CeO2 > 10PA-CeO2 > CeO2. The highest ethanol conversion and ethylene selectivity achieved were 65.8% and 99%, respectively, over the 30PA-CeO2 catalysts. The introduction of H3PO4 onto CeO2 catalyst helps in improving the catalytic performance of CeO2 for ethylene production from ethanol dehydration. In addition there was no carbon found in the spent catalysts which showed that the phosphorus modified cerium oxide catalysts have high coke resistance.